Towards the one : discipline and love explored through the new life and the inferno. - Ong, Hui Ling Cheryl. (2011)
Love and Discipline is explored in the Divine Comedy and The New Life, both works written by Dante Alighieri in the period of the Italian Renaissance. The thesis looks at how Dante plots the ascension to God in revolutionary ways and that by doing so, he has inspired other poets in this crafting of a personal vision, being a particular influence for poets in the Romantic Period. The paper locates Dante's source of inspiration in the philosophers Plotinus and St Augustine, as Neo-Platonist philosophy feature heavily in his works. Particularly, the paper pays attention to the structure of Hell and explores how the physical body is disciplined in the Inferno. Discipline is hierarchical and takes on literal meaning in the Inferno. Love for God is triggered first through the recognition of beauty in another person. This discipline and love draws one towards the higher realms and the individual gaze becomes increasing focused on the spiritual entities. By borrowing from antiquity and yet liberating himself from the influence of the church, Dante has shown himself to be a visionary who appears to be just beyond the canon of Renaissance writers. He is later to be admired by writers in the Romantic period, for this revolutionary personal interpretation of what salvation signifies.